The Effectiveness of Video Tutorial-Based Audiovisual Media on the Aspects of Prayer Movements in 5-6-Year-Old Children - Salsabila, Ana; Samawi, Ahmad; Astuti, Wuri (Al-Athfal: Jurnal Pendidikan Anak, 2023)
Purpose – The purpose of this study is to determine whether the use of audiovisual media in Group B at TK Muslimat NU 19 Malang affects children's knowledge of prayer movements before and after receiving treatment and to assess the effectiveness of this media. Design/methods/approach – This research employs an experimental research method with a comparative whole-group design. The research subjects consist of 30 children in Group B, comprising 14 boys and 16 girls, divided into experimental and control groups. Findings – However, after the treatment, their knowledge and skills in prayer movements improved to a good standard, based on a two-tailed signal of 0.892 in both the control and experimental groups, with a critical t-value of 0.682. It can be concluded that the significance value is greater than the critical t-value, rejecting the null hypothesis (H0) and accepting the alternative hypothesis (Ha). This demonstrates that the use of video tutorial-based audiovisual media influences the prayer movements' quality. The coefficient of determination (R2) shows a value of 0.671, indicating that 67.1% of the ability to apply religious values is influenced by audiovisual media for prayer movements, while 32.9% is influenced by other factors or variables. This suggests that the application of video tutorials is highly effective in enhancing children's knowledge and skills in performing prayer movements. Research implications/limitations – This study implies that introducing prayer in early childhood education can be done effectively with the use of audiovisual media. Practical implications – From a practical standpoint, this research provides examples of prayer movements in accordance with Islamic principles. Originality/value – The value of this research finding lies in the early introduction of prayer, assisted by audiovisual media. Paper type Case study